Degradation dynamics of surface earthworms casts in grasslands of the Eastern plains of Colombia - Decaëns, Thibaud (International Center for Tropical Agriculture, 2001)
Earthworms are generally considered to fulfill the definition of ecosystem engineers. The casts they produce are recognised to have a great importance in the regulation of soil processes. Lifetimes and degradation rates of these structures remain poorly known. In this study, the dynamics of disappearance and the changes in the physical properties of the surface casts of the anecic earthworm Martiodrilus carimaguensis were assessed in a native savanna and an intensive pasture. In both systems, casts were composed of superposed layers deposited by earthworms over a period of at least a few days. The half-life of casts ranged between 2 months to 11 months in the pastures (trampled and protected, respectively), and 5 months in the savanna. Some dry caets remained at the soil surface for more than I year after having been excreted. The disappearance of casts was mostly attributed to rain-drop impact and the effect of animal trampling. The bulk density of fresh casts was higher (+17%, P<0.05) or equivalent (-1%, P>0.05) to that of the surrounding soil, in the savanna and the pasture, respectively. Fresh cast aggregates were of larger size than bulk soil aggregates (about +70% in both systems, P<0.05). Bulk density and the size of cast aggregates decreased with cast ageing (from -29% to -24% for bulk density, and from -68% to -80% for size, in the pasture and the savanna, respectively). Macroinvertebrates were observed digging into casts, and were assumed to be partly responsible for the physical.